Sistem Pengelolaan Kegiatan Penelitian dan Pengabdian Masyarakat Menggunakan Framework Laravel - Windy; Widiantoro, Suryo (Fakultas Komputer - Universitas Universal, 2023)
Research and community service are one of the activities included in the threefold missions of higher education (Tri Dharma Perguruan Tinggi) in Indonesia that consists of 1) Education and Teaching, 2) Research and Development, and 3) Community Service. The current conditions at the university are still experiencing problems on controlling these activities because they are handled manually by the party concerned. As a result of this manual process, the activity process becomes inefficient and makes the existing process scattered and not managed properly. Therefore, this research is conducted to create a research information system and community service based on a website application to overcome these problems. With this website application, lecturers can easily submit research results quickly, reviewers can evaluate existing research also leaders can see the entire process of ongoing activities. Lecturers can also transparently see the existing assessment process and leaders have visibility of all ongoing activities.